(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The problems of training basics of binary technology creation while teaching differential equations and information-communication technology (ICT) based on the Maple-technology are researched. The relevance of the study is resulted from the basic contradiction between the latest opportunities of modern ICT, in particular Maple-technology and traditional methods of teaching mathematical disciplines, including differential equations. It is not enough only occasional applications of Maple-technology while conducting the lessons of mathematics. Mapletechnology opportunities allow to teach such differential equations by means of ICT. Thus it is necessary to solve the problem of the organic connection of traditional methods for solving differential equations and possibilities of Maple-technology regarding to the solving the generalization of high level. These actions include the simplification of the expression, solution of algebraic equations and systems, determining of eigenvalues and eigenvectors of matrices, differentiation and integration of scalar functions, vector functions and matrix functions, multiplication of matrix and matrix-vectors, the finding of the inverse matrix, etc. Binary classes are designed to teach mathematics and Computer science at the same time. Therefore, the creation of binary training technology is rather complicated problem. First of all, the teacher needs to develop an algorithm for determining the method for solving differential equations or systems of differential equations. This algorithm must consist of activities that can be automated in Maple-technology. Such actions are of a technical nature and do not have meaning-forming actions of a method of solving problems. Then efforts and attention to the subjects of the teaching will be directed to a method of solving the problem, the establishment of an appropriate algorithm and program in Mapletechnology. The creation and set-up of the program algorithm, is carried out simultaneously. After writing one or more operators you can run them and get the interim results. This will give the opportunity to set-up one or more operators, and see the result of their performance and immediately implement corrections in the right direction. Lectures can be carried out in such sequence. At first light the theoretical method for solving differential equations. It’s better to do it on the item at the same time creating an appropriate algorithm. In the basis of the algorithm creation the way of solving the equations should be put, and the actions which should be automated in the Maple-technology. The algorithm consists of a sequence of such actions execution.